2021
DOI: 10.1002/jcla.23721
|View full text |Cite
|
Sign up to set email alerts
|

KMT2D promotes proliferation of gastric cancer cells: evidence from ctDNA sequencing

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…KMT2D methylates lysine 4 in histone H3 in several cancers. [29][30][31] Our findings suggest that hsa_circ_0000977 may also promote the progression of esophageal cancer through the hsa_circ_0000977/miR-874-3p/KMT2D axis. However, there is a lack of reports on OSTIM in tumor-related mechanisms.…”
Section: And Kmt2dmentioning
confidence: 75%
“…KMT2D methylates lysine 4 in histone H3 in several cancers. [29][30][31] Our findings suggest that hsa_circ_0000977 may also promote the progression of esophageal cancer through the hsa_circ_0000977/miR-874-3p/KMT2D axis. However, there is a lack of reports on OSTIM in tumor-related mechanisms.…”
Section: And Kmt2dmentioning
confidence: 75%
“…When comparing the two groups, we found that the frequencies of mutations in KMT2B , SOX1 , and FGF12 were significantly higher in HBV-positive group than in HBV-negative group ( P = 0.035, Figure S3 and Figure 3B ), and the frequencies of mutations in KMT2D and TUBB2B showed an increasing mutated tendency in HBV-positive group than in the HBV-negative ( P = 0.315, Figure S3 and Figure 3B ), suggesting that these mutated genes may exert a biological impact on HBV-infected patients with GC. Recently, several studies had revealed that KMT2D ( Li et al., 2021 ; Numakura and Uozaki, 2021 ) and SOX1 ( Yin et al., 2020 ) were implicated in the initiation and progression of GC, whereas the other three frequently mutated genes have not been investigated. Thus, the mRNA expression levels of three frequently mutated genes in GC were analyzed by using TCGA datasets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high frequent mutations of KMT2D in high latitudes and the poor outcome in high latitudes were consistent with their results. Multiple studies have shown that mutations in these genes could influence the overall survival of GC patients ( Choi et al, 2015 ; Chen et al, 2019 ; Li et al, 2021 ; Yu et al, 2021 ). All these results suggest that the different mutational ratios of the same genes and the mutations in specific mutational genes might all be the causes of the difference between the two sample groups.…”
Section: Resultsmentioning
confidence: 99%